2006
DOI: 10.1002/hep.21230
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in primary biliary cirrhosis is associated with excessive daytime somnolence

Abstract: A significant proportion of patients with primary biliary cirrhosis (PBC) suffer from severe fatigue. The aim of this study was to characterize patterns of daytime sleep in patients with PBC (using both objective and subjective assessment approaches) and to study the association between sleep abnormality and fatigue severity. Fatigue severity was assessed in 48 female subjects with PBC (using a disease-specific quality of life instrument (the PBC-40) and a generic fatigue measure (Fatigue Impact Scale [FIS]) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 26 publications
4
122
1
1
Order By: Relevance
“…Taken together, these findings suggest that, whereas fatigue is a highly significant Control values are for an age-and sex-matched control population not preselected for symptom severity who completed a version of the PBC-40 (the PBC-40c) which was validated for completion by non-PBC patients for the purposes of this study and which was found to demonstrate construct validity (Supporting Table 1). In addition to the potentially generic symptom domains demonstrated in this figure, the impact of pruritus and general PBC symptoms was unsurprisingly greater in PBC patients than in matched controls (pruritus: PBC-40 pruritus domain score median 4 [interquartile range 0-9 in PBC patients versus 2 [0-3] in controls, P < 0.0001; general PBC symptoms 16 [12][13][14][15][16][17][18][19][20] versus 10 [8-13], P < 0.0001). Dotted lines for each symptom domain represent the cutoff for clinically significant symptoms (defined as mean value for normal subjects 12 SD).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Taken together, these findings suggest that, whereas fatigue is a highly significant Control values are for an age-and sex-matched control population not preselected for symptom severity who completed a version of the PBC-40 (the PBC-40c) which was validated for completion by non-PBC patients for the purposes of this study and which was found to demonstrate construct validity (Supporting Table 1). In addition to the potentially generic symptom domains demonstrated in this figure, the impact of pruritus and general PBC symptoms was unsurprisingly greater in PBC patients than in matched controls (pruritus: PBC-40 pruritus domain score median 4 [interquartile range 0-9 in PBC patients versus 2 [0-3] in controls, P < 0.0001; general PBC symptoms 16 [12][13][14][15][16][17][18][19][20] versus 10 [8-13], P < 0.0001). Dotted lines for each symptom domain represent the cutoff for clinically significant symptoms (defined as mean value for normal subjects 12 SD).…”
Section: Resultsmentioning
confidence: 97%
“…A score or 10 or over is regarded as indicating clinically significant daytime somnolence warranting intervention. 19 Orthostatic Grading Scale (OGS). Previous small studies have identified an increased prevalence of vasomotor autonomic symptoms in PBC (at early disease stages in addition to the well-recognized prevalence in cirrhotic disease).…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Sleep disturbance and excessive daytime somnolence are common in patients with cirrhosis [1,2,3,4]. In addition, a disturbance of sleep is recognized as one of the early signs of hepatic encephalopathy [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…5 Extreme fatigue might also be associated with excessive daytime somnolence. 6 Our patient complained of impaired quality of everyday life.…”
Section: Discussionmentioning
confidence: 87%